gag as well as myc sequences contribute to the transforming phenotype of the avian retrovirus FH3. - Tikhonenko, A T (1992)
The avian retrovirus FH3, like MC29 and CMII, encodes a Gag-Myc fusion protein. However, the FH3-encoded protein is larger, about 145 kDa, and contains almost the entire retroviral gag gene. In contrast to the other gag-myc avian retroviruses, FH3 fails to transform fibroblasts in vitro, although macrophages are transformed both in vitro and in vivo (C. Chen, B. J. Biegalke, R. N. Eisenman, and M. L. Linial, J. Virol. 63:5092-5100, 1989). We have used the polymerase chain reaction technique to obtain a molecular clone of FH3. Sequence analysis of the FH3 myc oncogene revealed a single proline----histidine change (position 223) relative to c-myc. However, substitution of the FH3 myc sequence with the chicken c-myc sequence did not alter the transformation potential of the virus. Hence, overexpression of the proto-oncogene as a Gag-Myc retroviral protein is sufficient for macrophage, but not fibroblast, transformation. After passage of FH3 in fibroblast cultures, a virus (FH3L) that is capable of rapidly transforming fibroblasts appears. The Gag-Myc protein encoded by FH3L is smaller (ca. 130 kDa) than that encoded by the original viral stock (FH3E). Sequencing of an FH3L molecular clone revealed a 212-amino-acid deletion within the Gag portion. Using FH3E/FH3L recombinants, we have demonstrated that the ability of encoded viruses to transform fibroblasts directly correlates with the presence of this deletion. Moreover, the addition of the Gag sequence deleted from FH3L to the MC29 oncoprotein significantly reduces its transforming activity as measured by focus assay. These data suggest that the C-terminal segment of Gag attenuates the oncogenic potential of Gag-Myc fusion proteins.